2020
DOI: 10.1016/j.jnucmat.2020.152360
|View full text |Cite
|
Sign up to set email alerts
|

Heavy ion irradiation damage in Zr3(Al0.9Si0.1)C2 MAX phase

Abstract: A Zr 3 (Al 0.9 Si 0.1 )C 2 MAX phase-based ceramic with 22% wt. ZrC and 10% wt. Zr 5 Si 3 has been irradiated with 52 MeV I 9+ ions at room temperature, achieving a maximum dose of 8 displacements per atom (dpa). The response of this MAX phase-rich material to irradiation has been studied using scanning electron microscopy, transmission electron microscopy and X-ray diffraction techniques. Post-irradiation examination of the material revealed a number of crystalline changes to the MAX phase. At low doses, Zr 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Most defects are annihilated during migration, which leads to relaxation of deformations and microstresses. However, at high irradiation densities, defect overlap regions are formed, which form regions with a nonequilibrium defect concentration, which leads to disordering and further amorphization of the structure and a decrease in the ceramic hardness along the entire ion path, as well as to the formation of additional optical traps and an increase in the photoionization cross section affecting the re ection ability of ceramics BeO [21,22]. However, the question still remains open related to the behavior of the structural and strength properties of BeO ceramics to high-temperature irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Most defects are annihilated during migration, which leads to relaxation of deformations and microstresses. However, at high irradiation densities, defect overlap regions are formed, which form regions with a nonequilibrium defect concentration, which leads to disordering and further amorphization of the structure and a decrease in the ceramic hardness along the entire ion path, as well as to the formation of additional optical traps and an increase in the photoionization cross section affecting the re ection ability of ceramics BeO [21,22]. However, the question still remains open related to the behavior of the structural and strength properties of BeO ceramics to high-temperature irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the past three years, Zr3AlC2 and Zr2AlC phases have been synthesized in bulk, but the materials still contain large amounts of ZrC phase [10][11] . Qarra, et al [12] investigated the heavy ion irradiation damage in Zr2AlC-rich material, and found that irradiated Zr2AlC was partially amorphous at room temperature but remained crystalline at high temperature.…”
mentioning
confidence: 99%